2008
DOI: 10.2337/dc07-1526
|View full text |Cite
|
Sign up to set email alerts
|

Should Nonalcoholic Fatty Liver Disease Be Included in the Definition of Metabolic Syndrome?

Abstract: OBJECTIVE -The ability of the Adult Treatment Panel III (ATP III) criteria of metabolic syndrome to identify insulin-resistant subjects at increased cardiovascular risk is suboptimal, especially in the absence of obesity and diabetes. Nonalcoholic fatty liver disease (NAFLD) is associated with insulin resistance and is emerging as an independent cardiovascular risk factor. We compared the strength of the associations of ATP III criteria and of NAFLD to insulin resistance, oxidative stress, and endothelial dysf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(110 citation statements)
references
References 34 publications
9
95
0
4
Order By: Relevance
“…39 Unlike other insulin sensitizers, such as thiazolidinediones, whose side effects may raise concern, the long-term safety of metformin is well established. 12,29,40 Our present findings are in agreement with results of Bugianesi et al, 18 who reported that metformin was more efficacious than dietary treatment on metabolic parameters in NAFLD patients and of Haukeland et al 41 , who found that the use of metformin was associated with weight loss and amelioration in the metabolic profile in NAFLD patients. Other studies have also found a beneficial effect of metformin on metabolic parameters, [15][16][17]41 and on liver enzymes and histology in NAFLD patients.…”
Section: Discussionsupporting
confidence: 92%
“…39 Unlike other insulin sensitizers, such as thiazolidinediones, whose side effects may raise concern, the long-term safety of metformin is well established. 12,29,40 Our present findings are in agreement with results of Bugianesi et al, 18 who reported that metformin was more efficacious than dietary treatment on metabolic parameters in NAFLD patients and of Haukeland et al 41 , who found that the use of metformin was associated with weight loss and amelioration in the metabolic profile in NAFLD patients. Other studies have also found a beneficial effect of metformin on metabolic parameters, [15][16][17]41 and on liver enzymes and histology in NAFLD patients.…”
Section: Discussionsupporting
confidence: 92%
“…Alguns autores consideram a presença da esteatose como a manifestação hepática da RI 13,15 . No estudo de Schwimmer et al 29 , as crianças e os adolescentes que apresentavam DGFNA tinham valores absolutos mais altos para marcadores de risco cardiovascular, além de maior frequência da SM.…”
Section: Discussionunclassified
“…Musso et al 13 verificaram associação positiva entre RI e DGFNA e também sugeriram a inclusão da DGFNA nos critérios para o diagnóstico da SM. D'Ádamo et al 14 , em estudo transversal com 100 crianças obesas e pré-púberes, encontraram prevalência de esteatose hepática de 52%.…”
Section: Introductionunclassified
“…11 Chan et al 12 conducted a systematic literature review and propose that non-alcoholic fatty liver disease (NAFLD) be acknowledged as a component of MS given that it is implicated in the context of risk factors for the development of type 2 diabetes mellitus and early-onset CVD. Musso et al 13 observed a positive correlation between IR and NAFLD and also suggested including NAFLD as diagnostic criteria for MS. D'Ádamo et al 14 carried out a cross-sectional study with 100 obese prepubertal children and found a prevalence of 52% for hepatic steatosis. Obese children with steatosis, when compared with the control group of normal-weight children and with obese children without steatosis, had higher HOMA-IR indices, which suggests an association between IR and steatosis.…”
Section: Metabolic Syndrome: Comparison Of Diagnosis Criteriamentioning
confidence: 98%